Enhancing Mechanical Properties of Alkali-Activated Slag SIFCON for Sustainable Construction Using Recycled Glass and Tire-Derived Waste Steel Fibers - Saadet Gokce Gok; Ozkan Sengul (International Journal of Concrete Structures and Materials)
Abstract This paper presents the outcomes of a study in which continuous steel fibers, recovered from scrap tires of vehicles, were used to prepare alkali-activated slag-based slurry infiltrated fibrous concrete (SIFCON). In this experimental study, the steel fibers used were 250 mm long, with varying fiber contents of 0%, 1%, 2%, 3%, 4%, and 5%. The alkali-activated SIFCONs were produced by activating ground granulated blast furnace slag (GGBS) with a mixture of sodium hydroxide (NaOH) and sodium silicate (Na2SiO3) solutions. Mixtures with ordinary Portland cement (OPC) were also cast for comparison purposes. The feasibility of utilizing finely ground waste glass as a silicate source for chemical activator solution in alkali-activated SIFCONs was also investigated. In this context, two different molar concentrations of NaOH, namely 8 M and 14 M, were employed during production. As activators, one series of mixtures utilized sodium hydroxide and sodium silicate solutions, while the other series replaced sodium silicate with finely ground waste glass. As a result, three different waste materials were utilized in concrete. 30 different mixtures were cast and examined in the experimental study. Load–deflection curves were obtained in three-point bending test and mechanical properties of the mixtures such as compressive, splitting and flexural strengths, fracture energy, and toughness were determined. The flexural strength and toughness increased with the use of waste steel fibers. The continuous waste fibers derived from discarded tires yielded results comparable to commercially available fibers, demonstrating their effectiveness in enhancing mechanical properties. Depending on mix design, the alkali-activated SIFCON attained flexural strength exceeding 75 MPa and compressive strength surpassing 100 MPa. These results suggest that concretes incorporating a variety of waste materials can be effectively combined. This innovative approach bridges an existing gap in the literature by combining alkali activation, waste glass, and waste steel fibers, ultimately yielding a sustainable composite that outperforms normal concretes in terms of mechanical properties while promoting environmental sustainability. Test results demonstrate that it is possible to obtain concrete with comparable mechanical properties while primarily composed of by-products and waste materials. This approach marks a substantial step in achieving high-performance concrete that relies solely on waste or by-products. Graphical Abstract